Identification of Ectomycorrhiza-Associated Fungi and Their Ability in Phosphate Solubilization - Mujahidah, Shofia; Sukarno, Nampiah; Kanti, Atit; Sudiana, I Made (JURNAL BIOLOGI INDONESIA, 2018)
ABSTRACTThe existence of Pinus sp. is very dependent on ectomycorrhizal (ECM) fungi. ECM fungi affect the growth of their hosts especially by increasing mineral availability and water intake. However ECM fungi is not the only one that plays a role in the growth of their host. There are many ECM-associated fungi which also have many important roles in the growth of the host. Helotiales which were isolated from the ECM of Pinus merkusii are known as the most member of root associated fungi. Three isolated Helotiales identified as Scytalidium sp., Helotiales sp., and Glutinomyces sp. by morphological and molecular identification based on ITS1, 5.8S rRNA, ITS2 DNAr region. All three isolates have the ability to solubilize phosphate. Compared with C. geophilum which already known as P solubilizing fungi, Glutinomyces solubilized 16.6 ppm P which is higher than C. geophilum which solubilized as much as 13.68 ppm in Pikosvkaya medium with glucose as carbon source and rock phosphate as phosphate source. Then followed by Scytalidum sp. and lastly Helotiales sp. Rock phosphate tend to harder to solubilize because its complex chemical form with other minerals. Keyword: ECM-associated fungi, Helotiales, phosphate solubilizing ability, Pinus merkusii